Wheelchair use confidence scale for Arab pediatric manual wheelchair users: preliminary evaluation of its measurement properties - Sarsak, Hassan Izzeddin; Rushton, Paula W. (Frontiers in Pediatrics, 2025)
IntroductionThis study translated the pediatric Wheelchair Use Confidence Scale for Manual Wheelchair Users (WheelCon-M-P) into Arabic (WheelCon-M-A-P) and evaluated whether the translation produced scores similar to the original English version.MethodsThe English version was first translated into Arabic and then verified by back translation method by expert committee in the field of rehabilitation and wheelchair service provision. The final versions were administered to assess confidence with manual wheelchair use among children. Each participant was asked to complete both the WheelCon-M-P English version and the WheelCon-M-A-P Arabic version in a random sequence. Kappa statistics were used to quantify the level of agreement between scores obtained from both versions.ResultsParticipants (n = 48) had an average age of 14.2 years, were all bilingual, and 54% were male. Kappa agreement obtained was 0.54 (95% confidence interval, 0.49–0.62) indicating significant moderate agreement between the two versions (p < 0.000).DiscussionThis study provides preliminary evidence of a valid WheelCon-M-A-P to assess confidence with manual wheelchair use among Arabic-speaking children. Future studies to further test its psychometric properties are crucial.